Report on Candidates' Work in the Secondary Education Certificate General and Basic Proficiency Examinations June 1990: Clothing and Textiles - Caribbean Examinations Council (Caribbean Examinations Council (CXC), 1990)
This report contains general and specific comments on the performance of candidates in June 1990 Caribbean Secondary Education Certificate Examination (CSEC) in Clothing and Textiles at the general and basic proficiency levels.
Keywords: Clothing and textiles; CSEC